The Importance of Social Entrepreneurship for the Labour Integration of Convicted Persons - Mihajlović, Aleksandar (Zbornik Instituta za kriminološka i sociološka istraživanja, 2023)
Social entrepreneurship, as an innovative form of business that combines market principles of functioning, as well as a special social role to overcome certain life difficulties faced by members of various vulnerable social groups, for the first time, received its normative framework in the Republic of Serbia with the adoption of the Law on Social Entrepreneurship. The subject of this paper is social entrepreneurship in the context of labour integration of convicted persons, and this research aims to indicate to what extent this new legal framework can be applied as a kind of post-penal assistance in the Republic of Serbia. The Law on the Execution of Criminal Sanctions and the Law on the Execution of Extra-Communal Sanctions and Measures provide that post-penal assistance after a convicted person’s release from prison includes support related to integration into the labour market, but without further details on how this would be achieved. Therefore, social entrepreneurship after the adoption of the concrete law in 2022 in the Republic of Serbia should be used as an instrument for the labor integration of convicted persons. Additional observation of this perspective of social entrepreneurship with a suitable public policy document would contribute to better planning and creation of measures aimed at achieving the desired results (reduction of recidivism rate), as well as monitoring the effectiveness and efficiency of the application of adopted legal solutions from the new regulation.